Pluralistic co-existence and the role of comparative religion in Islamic higher education in context of Malaysia - Kamaruzaman, Kamar Oniah (IIUM Press, 2015)
One of the concerns, if not fears, of nations and communities in this Age of Globalisation is that they may be swallowed up by the waves of globalisation, thus losing their national and communal identities, and flattened out to be a stereotype with all others.